Skating in West Galicia in 1867–1914 period - Krasowski, Robert; Nadolski, Waldemar (Sport and Tourism Central European Journal, 2019)
In the second half of the 19th century skating was the only winter sport practised by the majority of social classes of West Galicia. Skating rinks located in the biggest city of the area in question, Kraków, were very popular. Later on, skating rinks in Tarnów, Rzeszów and Nowy Sącz or Wadowice also gained in popularity. The first skating competition was held in Krakow in 1881. However, up until 1890 skating was mainly seen as an enjoyable winter social entertainment. Since 1890, State School Committee (Rada Szkolna Krajowa) made school institutions introduce few sports into their curriculum i.e. skating. Since then, skating has become widely popular. Additionally, outdoor sporting activities were encouraged by newly established „falcon’s nests” that trained teachers of gymnastics and opened their own skating branches. After 1900, skating sport was practised basically in every town of West Galicia, although it started to become less popular, becoming replaced with ski lunge and skiing. Undoubtedly, in 1867–1914 period Kraków was the center of skating sport in West Galicia.